Stepping into emotionally focused therapy : key ingredients of change - Brubacher, Lorrie L. (New York, NY : Routledge, 2024)
"This accessible, practical, and thoroughly updated second edition introduces and presents how emotionally focused therapy can be used effectively across all three modalities, couple, family, and individual therapy, with clients from a diversity of backgrounds. Responding to critical updates in the field, this second edition once again follows Emily, an EFT therapist, to demonstrate how EFT can be used in practice. With updated references, research, and terminology throughout, this new edition reflects recent theoretical and practical updates by refocusing the model towards therapist macro interventions, such as the 'EFT Tango', rather than the client change events, making it more accessible for readers to learn. It addresses the current need to integrate explicit sociocultural sensitivity into EFT by including diverse case studies, explicit discussion of how the model can be applied with a diversity of clients, and how EFT therapists can integrate cultural sensitivity and attunement across multiple and diverse identities, such as race, gender, sexual orientation, disabilities, neurotypicality, class, and religion. It can also be used alongside a practical new workbook, Workouts for Stepping into Emotionally Focused Therapy, providing therapists with all the tools needed to integrate this approach in their practice confidently. This book is an essential read for all marriage and family therapists in practice and in training as well as counsellors who are looking to use EFT with couples, families, and individuals"--
Earlier edition published in 2018 as: Stepping into emotionally focused couple therapy.
Keywords: Emotion-focused therapy; Couples therapy; Family psychotherapy; Psychotherapy; PSYCHOLOGY / Psychotherapy / Couples & Family; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / General